2014
DOI: 10.1007/s00330-014-3500-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of diffusion-weighted imaging, apparent diffusion coefficient and correlation with hepatobiliary phase findings in the differentiation of hepatocellular carcinoma from dysplastic nodules in cirrhotic liver

Abstract: • Usefulness of DWI and ADC is shown in differential diagnosis of cirrhotic nodules. • Correlation of DWI with DPI improves differential diagnosis of cirrhotic nodules. • Characterization of atypically enhancing lesions becomes more confident.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 36 publications
(36 reference statements)
0
42
0
Order By: Relevance
“…Alongside with other functional imaging modalities, such as 18-flourdeoxyglucose positron emission tomography/computed tomography (FGD-PET/CT), the diffusionweighted imaging (DWI) derived apparent diffusion coefficient (ADC) has been identified as a prognostic imaging biomarker (Charles-Edwards and deSouza 2006). DWI has shown promising results in differentiating tumor subtypes and histopathological patterns of tumor aggressiveness (Inchingolo et al 2015). It has been demonstrated that morphological tumor response of common primary cancers and liver metastases was associated with ADC changes after both systemic and locoregional interventional therapies (Kukuk et al 2014;Liang et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Alongside with other functional imaging modalities, such as 18-flourdeoxyglucose positron emission tomography/computed tomography (FGD-PET/CT), the diffusionweighted imaging (DWI) derived apparent diffusion coefficient (ADC) has been identified as a prognostic imaging biomarker (Charles-Edwards and deSouza 2006). DWI has shown promising results in differentiating tumor subtypes and histopathological patterns of tumor aggressiveness (Inchingolo et al 2015). It has been demonstrated that morphological tumor response of common primary cancers and liver metastases was associated with ADC changes after both systemic and locoregional interventional therapies (Kukuk et al 2014;Liang et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This discrepancy may be explained by the spectrum of DNs and HCCs and their spectrum of signal intensities on the HBP. Inchingolo et al showed that the signal intensity on DWI and HBP was useful in the differentiation between HCCs and DNs, and between HCCs plus high-grade DNs and low-grade DNs [61]. For cirrhotic nodules with atypical vascular enhancement patterns, Golfieri et al reported that hypointensity on the HBP was predictive of malignancy [62].…”
Section: Hcc Vs Other Hepatocellular Nodulesmentioning
confidence: 99%
“…The nodules were further reorganized into three groups. A group of benign nodules included the regenerative and low‐grade dysplastic nodules, a group of nodules with intermediate malignancy included the high‐grade dysplastic nodules and early hepatocellular carcinomas, and a group of progressed hepatocellular carcinomas included overt, moderately, or poorly differentiated hepatocellular carcinomas, as previously proposed …”
Section: Methodsmentioning
confidence: 99%
“…The characterization of these nodules is important for determining patient prognosis and allowing the best treatment at an early stage . It has been suggested that cirrhotic hepatic nodules be classified into three groups based on their relative malignant potential: a benign group consisting of regenerative nodules and low‐grade dysplastic nodules, a group of nodules with intermediate malignancy consisting of high‐grade dysplastic nodules and early hepatocellular carcinomas, and a group of overtly malignant lesions consisting of progressed hepatocellular carcinomas …”
mentioning
confidence: 99%